Computational Thinking Improvement Through Speech Recognition Application Development for Pahoa High School Students: Peningkatan Computational Thinking Melalui Pengembangan Aplikasi Speech Recognition Bagi Siswa SMA Pahoa - Theresia Herlina Rochadiani; Handri Santoso (Universitas Lancang Kuning, 2023)
Computational Thinking (CT) skills are needed in jobs in the Industrial 4.0 era. Activities to improve CT have been widely carried out in the world of education. Learning programming and artificial intelligence education is one of the ways to improve CT. This community service activity (PkM) at Pahoa High School aims to improve CT through the development of a speech recognition application using the MIT App Inventor. Through the stages of goal setting, the need for students is defined. Then in the preparatory stage, training modules are drawn up. At the implementation stage, PkM activities are carried out online and as an evaluation stage, at the end of the activity students are given a test. This activity was followed by 44 students online. As the results, 68% of students received test scores of more than 60 and an average of 70% of students answered correctly questions related to algorithm design.